Manifestations of economic integration consequences in Lithuanian foreign trade - Žitkienė, Rima; Žitkus, Leonas (Business: Theory and Practice, 2011)
Changes of directions and volumes of Lithuanian foreign trade during the last fifteen years are analyzed in the article. They are understood as the consequences of Lithuania’s integration into the EU, which are provided by economic integration theories. The paper consists of introduction, two parts and conclusions. The first part identifies the changes of Lithuanian foreign trade (trade creation and trade diversion) as part of the whole integration consequences system. On the basis of statistic data the scale and directions of trade creation and diversion caused by particular outline of Lithuania’s integration – European Treaty enforcement in 1998 and entering the European Union in 2004 – are revealed in the second part. In both cases certain changes occurred in foreign trade – trade diversion refusing one partner and orienting to others as well as trade revival with particular partners. Those changes are named as the proof of Lithuania’s economy as the whole and its subjects (enterprises) ability to react to the changes caused by integration processes, which is disclosed in the conclusions.